Implementasi Manajemen Strategis dalam Meningkatkan Peran Serta Masyarakat di SMK Darur Roja Cinere Depok - Ukat Suhaedi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This study aims to analyze the implementation of strategic management in enhancing community participation at SMK Darur Roja Cinere Depok. The research was motivated by the low level of active community involvement in educational activities, particularly in faith-based vocational schools. Using a qualitative approach and case study method, data were collected through in-depth interviews, participatory observations, and documentation. The findings indicate that strategy formulation was conducted participatively, involving the principal, teachers, the school committee, and the surrounding community. The strategic implementation included various collaborative programs such as "Parents Teach," partnerships with local businesses, and community involvement in religious and entrepreneurship activities. Evaluation of the implemented strategy revealed a significant increase in community participation in moral, financial, and operational aspects. Despite existing structural and cultural challenges, strategic management has proven effective in strengthening reciprocal relationships between the school and the community. This study recommends improving public communication capacities and developing more contextual collaborative models for managing community-based education.